Advanced structural analysis of reinforced shotcrete barricades - Grabinsky, MW; Cheung, D; Bentz, E; Thompson, BD; Bawden, WF (Mine Fill 2014: Proceedings of the Eleventh International Symposium on Mining with Backfill, 2014)
Several attempts have been made to assess the ultimate capacity, and sometimes the overall response, of cemented mine fill barricades. Many of these have incorporated elastic-plastic constitutive models which are known to be inferior when modelling non-linear plain or reinforced concrete behaviour. Furthermore, virtually all such studies have not systematically considered the surrounding host rock’s stiffness. This paper considers barricades with boundaries of both infinite and finite stiffness using advanced numerical analysis tools developed at the University of Toronto which have been specialised for reinforced concrete design in a civil engineering context. These peer-reviewed tools are internationally considered to be state-of-the-art. The first case considers the problem of modelling reinforced concrete barricades with infinitely stiff boundary conditions. A set of relevant, carefully controlled laboratory studies is reviewed and the numerical analysis technique is shown to be appropriate. Modelling is then carried out for the case of a barricade at Cayeli Mine where the loading was believed to be essentially fluid, and therefore the modelled boundary condition easily represented. The pre-peak load-deformation relationships are correlated between field monitoring and numerical model results with excellent agreement. The second case considers the problem of barricade boundaries with finite stiffness. Equations based on Timoshenko and Boussinesq solutions were developed to represent equivalent end restraints for the modelled barricade. A wide range of stiffness encompassing virtually all possible rock conditions was considered. Practicing mining engineers can use standardised underground mapping and rock mass classification techniques to determine what an appropriate end stiffness value would be for their mining conditions. It will be shown that barricade capacity varies significantly with host rock stiffness, and that the commonly made design assumption of a fully rigid boundary can result in unconservative over-prediction of barricade strength.